The Directions of FinTech Development in Russia: Expert Opinion of the Financial University - M. A. Eskindarov; M. A. Abramova; V. V. Maslennikov; N. A. Amosova; A. V. Varnavskii; S. E. Dubova; E. A. Zvonova; S. V. Krivoruchko; V. A. Lopatin; V. Ya. Pishchik; O. S. Rudakova; G. F. Ruchkina; et al. (Мир новой экономики, 2018)
The active digitalization of the life of modern society observed over the past 20 years has led to real changes in the economy. The financial sector is at the heart of a digital transformation that has been spearheaded by FinTech, which is now shaping a new segment of modern financial markets. At the same time, the most wellknown objects of FinTech are cryptocurrency and token. Cryptocurrencies, regardless of the attitude of regulatory authorities to them, have become a virtual reality of the financial sector and are actively used to pay for goods and services. The peculiarity of cryptocurrencies is its anonymity and unaccountability of the state that defines a range of risks to society and the state. However, cryptocurrencies, along with risks, create opportunities — from the development of innovative technologies to the creation of new jobs and replenishment of the national budget. The penetration of FinTech into the financial market segments traditionally occupied by banks gave rise to a discussion about their future. However, it will probably not be the displacement of the banks but their FinTech transformation. An example of this is the payment industry, which has become one of the main consumers of the latest financial technologies and provides a wide range of opportunities for FinTech companies to develop. An important element of FinTech is RegTech (Regulatory Technology), which allows companies to bypass trade barriers and helps build a constructive dialogue with regulators. In turn, SupTech (Supervision Technology) is used for analysis and forecasting purposes. At the end of the article, based on the analysis of foreign experience, we formulated the main approaches, the implementation of which allows states to stimulate the introduction and development of new financial technologies, as well as we analysed the experience of interstate coordination of cooperation in the field of financial technologies in the EU and the EAEU countries.